Prevalence of metabolic syndrome in veterans with spinal cord injury. (2nd January 2019) - Gater, David R.; Farkas, Gary J.; Berg, Arthur S.; Castillo, Camilo
Abstract : Context/Objective: Recent literature would suggest the prevalence of metabolic syndrome in persons with spinal cord injury (SCI) is higher than that of the general population, although no large cohorts have yet been reported. Part of the controversy relates to the differing definitions provided for metabolic syndrome and the characterization of obesity in persons with SCI. Design/Participants: The current retrospective investigation represents a cross-sectional cohort of 473 veterans with SCI from a single center in the mid-Atlantic region of the United States for whom modified International Diabetes Federation (IDF) criterion variables for the metabolic syndrome were available in the computerized personal record system (CPRS). Outcome Measures: These variables included a surrogate marker of obesity appropriate to SCI (Body Mass Index (BMI) ≥ 22 kg/m 2 ), as well as indicators of diabetes, dyslipidemia and hypertension. Results: Over 57% of the veterans assessed were determined to have metabolic syndrome by modified IDF criteria, including 76.7% with BMI ≥ 22 kg/m 2, 55.1% with or under treatment for hypertension, 49.7% with or previously diagnosed with diabetes mellitus, and 69.7% with or under treatment for high density lipoprotein (HDL) cholesterol under 40 mg/dl. Conclusion: Metabolic syndrome and its constituent components appear to be more prevalent in veterans with SCI than in the general population, suggesting a greater need for identification and treatment interventions in this specialty population.